At Lincoln's side : John Hay's Civil War correspondence and selected writings - Hay, John, 1838-1905 (Southern Illinois University Press, 2000)
John Hay believed that "real history is told in private letters," and the more than 220 surviving letters and telegrams from his Civil War days prove that to be true, showing Abraham Lincoln in action: "The Tycoon is in fine whack. I have rarely seen him more serene & busy. He is managing this war, the draft, foreign relations, and planning a reconstruction of the Union, all at once. I never knew with what tyrannous authority he rules the Cabinet, till now. The most important things he decides & there is no cavil."Along with Hay's personal correspondence, Burlingame include.